Herbal formulation MIT ameliorates high-fat diet-induced non-alcoholic fatty liver disease - Ahn, Sang-hyun (Integr Med Res, 2020)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) is one of the most common liver diseases and is caused by obesity, diabetes, high blood pressure, and insulin resistance. Many studies have explored novel candidates to treat NAFLD using herbal medicines owing to their fewer side effects. In this study, we examined the effect of MIT, an herbal formula comprising Ephedra sinica, Panax ginseng, and Alisma orientale, on the murine model of NAFLD. METHODS: To evaluate the effect of MIT on NAFLD, we used the high-fat diet (HFD)-induced NAFLD mice model. The mice were divided into four groups: control, HFD, HFD with metformin administration, and HFD with MIT administration. Freeze-dried MIT was dissolved in phosphate buffered saline and orally administered for 8 weeks to MIT-treated mice (60 mg/kg) after feeding them with HFD for 16 weeks. RESULTS: MIT treatment significantly attenuated fat accumulation, serum glucose levels, and excessive cholesterol. It also reduced the activation of NF-κB, JNK, ERK, mammalian target of rapamycin, and peroxisome proliferator-activated receptor γ in the HFD-induced NAFLD mice. The expression level of enzymes involved in the synthesis and oxidation of fatty acids, acetyl-coA carboxylase and CYP2E1, were clearly reduced by MIT treatment. Reactive oxygen species (ROS) production and subsequent liver damage were effectively reduced by MIT treatment. CONCLUSION: We suggest that MIT is a potent herbal formula that can be used for the prevention and treatment of obesity-related NAFLD via regulating the levels of serum glucose and free fatty acids, inflammation, lipid accumulation, and ROS-mediated liver damage.